2007
DOI: 10.1002/chin.200729231
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Synthesis of O‐Glycosides of 2‐Amino‐2‐deoxysugars

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In contrast to the large number of studies devoted to the synthesis of linear oligosaccharides with β(1f4)linked 2-amino-2-deoxy-D-glucopyranose units, efficient and practical methods for the synthesis of analogous oligosaccharides with β(1f4)-linked 2-amino-2-deoxy-D-galactopyranose units remain scarce. Glycosylation 27 (22) promoted by silver perchlorate in the presence of silver carbonate gave a complex mixture of reaction products. Only few reports on disaccharide syntheses of this type have been published so far, and these used a glycosyl acceptor having the azido group as the masked amino function at the C(2) position and 2-deoxy-2-phthalimido-D-galactopyranosyl bromide as the glycosyl donor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the large number of studies devoted to the synthesis of linear oligosaccharides with β(1f4)linked 2-amino-2-deoxy-D-glucopyranose units, efficient and practical methods for the synthesis of analogous oligosaccharides with β(1f4)-linked 2-amino-2-deoxy-D-galactopyranose units remain scarce. Glycosylation 27 (22) promoted by silver perchlorate in the presence of silver carbonate gave a complex mixture of reaction products. Only few reports on disaccharide syntheses of this type have been published so far, and these used a glycosyl acceptor having the azido group as the masked amino function at the C(2) position and 2-deoxy-2-phthalimido-D-galactopyranosyl bromide as the glycosyl donor.…”
Section: Resultsmentioning
confidence: 99%
“…20 Moreover, we have shown that the complex pentaantennary bisecting undecasaccharide from egg white glycoprotein ovomucoid with the structure [GlcNAcβ1-2(GlcNAcβ1-4)(GlcNAcβ1-6)-ManR1-6][GlcNAcβ1-2(GlcNAcβ1-4)ManR13][GlcNA-cβ1-4]Manβ1-4GlcNAcβ1-4GlcNAc (OM, Chart 1), is one of the best ligands of natural origin identified so far. 22,23 Recently, we synthesized the branched homotrisaccharide β-D-GlcNAc-(1f3)[β-D-GlcNAc-(1f4)]-D-GlcNAc and found that its binding affinity for NK cell lectin receptors competed successfully with oligosaccharides of much greater complexity. This natural structure has thus provided an important paradigm for the development of smaller synthetic oligosaccharide mimetics that would be accessible for large scale synthesis and further potential use for in vivo experimental tumor therapies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…164 However, despite the high regioselectivity of this reaction, a mixture of epimers 34 and 35 was observed in varying ratios based on the employed glycal substrate 33 (Scheme 12). 165 The prepared nitropyranoses 34 and 35 may find significance in preparation of numerous carbohydrate-based halides, thioglycosides, etc. 166−170 Likewise, 2-azido sugars can also be prepared by azidochlorination, 171 azidophenylselenation, 172,173 and diazo transfer reaction.…”
Section: Azides and Alkyne Substrates: Benefit For Carbohydratesmentioning
confidence: 99%
“…(Holtje, 1998) The lack of pure PGN fragments, PGN derivatives or its mimetics, has strongly hampered the investigation of the relevance of the PGN structure in the metabolism of bacteria and the determination of its role in host disease.(L. H. Wang et al, 2006) The synthesis of NAG containing oligosaccharides, such as NAG-NAM disaccharides, (Berthelot et al, 2017;Shih, Chen, Cheng, Wong, & Cheng, 2011;Yang et al, 2011;Yang & Yu, 2014) presents several challenges, such as: the enantioselective establishment of the -(1,4)-glycosidic bond; the use of 2-acetamido-2deoxyglycosyl donors, that lead to formation of 1,2-O,N-oxazoline intermediates, (Arihara, Nakamura, & Hashimoto, 2005;Bongat & Demchenko, 2007;R. Enugala, Carvalho, Pires, & Marques, 2012;Stevenin, Boyer, & Beau, 2012) and the use of corresponding acceptors that are poor nucleophiles.…”
Section: Introductionmentioning
confidence: 99%